Effect of flyer speed on yarn breakages in production of jute yarn (Daffodil International University Journal of Science and Technology, 2010)
In Bangladesh, jute mills are producing conventional yarns heavier than 275 tex. These are used as hessian, sacking, carpet backing cloth etc. For diversified uses of jute it is most essential to produce medium count yarn of 241 to 275 tex. In this regard, slip draft spinning machine has been studied. This machine is capable to produce yarn of 241 to 280 tex at flyer speed of 2900 rpm to 4850 rpm. But there is a relation between flyer speed and yarn breakages of the machine. In addition spinning efficiency of the machine also depends on the yarn breakages. Through a series of experiment, a relation has been established between flyer speed and yarn breakages of the experimental machine for production of jute yarn. From the experimental observation, it shows that for production of 241 tex jute yarn 4700 rpm flyer speed is the most suitable speed and 4800 rpm flyer speed is the most suitable speed for production of 275 tex jute yarn. In addition productivity of the machine also maximum at that flyer speed of the machine. In this experimental study, it was found that at 4850 rpm it was very difficult to spin yarn due to its random breakages. That consequently lowered the productivity. Therefore, it is necessary to select proper flyer speed for the production of yarn of particular linear density (tex). It was also observed that the number of breakages increased with the increase of flyer speed. At 2900-rpm flyer speed, the yarn breakage was 0.8/ spindle-hr and at 4850 rpm the yarn breakages is 3.5/spindle-hr. for producing 241 tex jute yarn. Almost all jute mills of Bangladesh have been slip draft spinning machine. Using proper flyer speed, which was found from the experiment, can use the machine in production of medium count jute yarn. The produced yarn can replace the synthetic/manmade fibre in the world textile market. Key Words: Spinning, Tex, Productivity, yarn and Breakages.   DOI: 10.3329/diujst.v4i2.4364 Daffodil International University Journal of Science and Technology Vol.4(2) 2009 pp.23-27